Sinouos link (2002)
Puente peatonal que permite vinculacion de una escuela sobre una calle, por los arqs. <Birds Portchmouth Russum>, en Londres
Keywords: PUENTES; PUENTES PEATONALES; LONDRES; INGLATERRA